2016
DOI: 10.12988/es.2016.631
|View full text |Cite
|
Sign up to set email alerts
|

Desert aerosol optical properties in Morocco

Abstract: Moroccan weather and climate are influenced by desert winds coming from South-East and by Atlantic advections. The annual cycle of seasonal average of aerosol optical depht shows similar values in Oujda and Saada and registers higher values in Ouarzazate, due to different weather conditions. The maximum values are recorded in summer near 0.25 (Oujda, Saada) and 0.34 (Ouarzazate). The seasonal average of the refraction index varies with the seasons, the component relating to scattering at 0.44 microns varies li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…They also found that urban and biomass burning aerosols were of local origin. The most recent published work on Morocco was reported by Tahiri et al [18,19]. They analyzed two AOD datasets measured at Saada (31.63°N; 8.16°W) and Ouarzazate (30.93°N; 6.91°W), two of the study sites of the present manuscript, over two successive years: 2012 and 2013.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…They also found that urban and biomass burning aerosols were of local origin. The most recent published work on Morocco was reported by Tahiri et al [18,19]. They analyzed two AOD datasets measured at Saada (31.63°N; 8.16°W) and Ouarzazate (30.93°N; 6.91°W), two of the study sites of the present manuscript, over two successive years: 2012 and 2013.…”
Section: Introductionmentioning
confidence: 93%
“…Ouarzazate is a small town located east of the Atlas Mountains and north of the Sahara Desert, with almost no industrial activity. It has a pre-Saharan climate characterized by low rainfall with hot and dry summers [19]. The Saada and Ras-El-Aïn stations are located ∼15 km from the city of Marrakech and ∼60 km west of the Atlas Mountains.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Tetouan, which is located in the north of Morocco on the Mediterranean coast, has a low concentration. Tinfou, a station located in the Sahara, has a high concentration due to its proximity to the source of natural dust emission (Knippertz et al, 355 2007;Tahiri et al, 2016). The urban concentration of Moroccan cities remains low compared to Delhi in India, for example, which has a concentration of about 232 µg/m 3 .…”
Section: Comparison With Other Stationsmentioning
confidence: 99%
“…In addition to their effects on cloud properties and precipitation [28], dust aerosols play important roles in biogeochemical cycles [29], atmospheric chemistry [30], visibility, and human health [31]. Various photometric measurement campaigns allowed to determine the desert dust volume size distribution with a radius between 0.05 and 15 µm [32,33], but for a limited period of time, no longer than 2 years of observation. According to Tahiri et al [33], from 2013 AERONET measurements, the volume size distributions at 3 Moroccan sites (Oujda, Saada, and Ouarzazate) showed the same shape with median radii around 0.15 µm for fine particles and 2.59 µm for coarse particles.…”
Section: Introductionmentioning
confidence: 99%